THE IMPLEMENTATION OF MULTIPLE INTELLIGENCE LEARNING MODEL WHICH IS ORIENTED TO STUDENTS’ PARTICIPATION IN ACADEMIC WRITING (The Journal of Educational Development, 2015)
This study aims to describe the student's and lecturer's needs related to the improvement of learning quality of academic writing; the level of acceptability of multiple intelligence learning model which is oriented to the studentsâ€™ participation (KMP) on the content substance,thestructure flexibility of modeldesign, and the effectiveness of learning model of multiple intelligenceswhich is oriented to student's participation on the improvement of theiracademic writing. To test the fit models or hypothetical model conceptually and theoretically,this study was supported by empirical data and instruments with students as respondents. The data was then analyzed using confirmatory factor analysis (CFA) by Lisrel program. Teachers as respondents instrument was analyzed through factor analysis using SPSS for windows. The development of the model used descriptive, evaluative, and experimental models, and also quantitative test using structural equation modeling (SEM) by Lisrel program. The output of the research result is a draft model of KMP validated by a team of experts with the average score of 3.70 (being able to be usedwith minor revision). KMP model is rated as a good model (4:02) viewed from its comprehensiveness, practicality, and economy. The analysis of appropriateness hypothetical test between models and data fields based on the implementation of data shows that a) all variables seem to have value (Î»)> 0.3; b) Chi - Square = 0.61, df = 1, Ï - value = 0:43 (> 0.05); c) RMSEA is 0.00 (<0:08); and d) GFI = 0.99 (> 0.90). The result of analysis shows that there is compatibility between KMP model and the field data. The average of the ability of critical-creative thinking of experiment 3 for the control group is 68.31, while the experimental group is 74.88. It means that the treatment of KMP influences the learning process. The result of tcount = 15 066> t table = 1.98. The difference of the average score is sated significant and proved effective in improving the ability of academic writing.